2011
DOI: 10.1093/hmg/ddr505
|View full text |Cite
|
Sign up to set email alerts
|

A novel mouse model of Niemann–Pick type C disease carrying a D1005G-Npc1 mutation comparable to commonly observed human mutations

Abstract: We have identified a point mutation in Npc1 that creates a novel mouse model (Npc1(nmf164)) of Niemann-Pick type C1 (NPC) disease: a single nucleotide change (A to G at cDNA bp 3163) that results in an aspartate to glycine change at position 1005 (D1005G). This change is in the cysteine-rich luminal loop of the NPC1 protein and is highly similar to commonly occurring human mutations. Genetic and molecular biological analyses, including sequencing the Npc1(spm) allele and identifying a truncating mutation, conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
160
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(179 citation statements)
references
References 61 publications
19
160
0
Order By: Relevance
“…Homozygous mutants of both strains (Npc1 Ϫ/Ϫ ) along with wild type littermates (Npc1 ϩ/ϩ ) were generated by crossing heterozygous mutant (Npc1 ϩ/Ϫ ) males and females in house. Npc1 nih mouse pups were genotyped according to published protocols (8), and Npc1 nmf164 mice were genotyped based on PCR followed by digestion with BstEII (29). In this study, unless otherwise indicated, Npc1 nih mice were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Homozygous mutants of both strains (Npc1 Ϫ/Ϫ ) along with wild type littermates (Npc1 ϩ/ϩ ) were generated by crossing heterozygous mutant (Npc1 ϩ/Ϫ ) males and females in house. Npc1 nih mouse pups were genotyped according to published protocols (8), and Npc1 nmf164 mice were genotyped based on PCR followed by digestion with BstEII (29). In this study, unless otherwise indicated, Npc1 nih mice were used.…”
Section: Methodsmentioning
confidence: 99%
“…We further examined plasma from Npc1 nmf mouse. Previous studies suggested that Npc1 nmf mice in the C57BL/6J background have a life span of ϳ112 days and develop progressive disease (29). BALB/c Npc1 nmf have a comparable life span (ϳ120 -125 days) and exhibited weight loss from 85 to 90 days (19).…”
Section: (Fig 1c Panels I-iii)mentioning
confidence: 99%
“…These mice are asymptomatic at birth but develop ataxia and die within ‫ف‬ 3 months. A more recent mouse model carries the D1005G mutation in NPC1 ( 73 ). This mutation is in the cysteinerich loop of NPC1, the site at which the most common mutations occur in human NPC patients, and these mice have a more slowly progressing disease than that of NPC1-null by guest, on May 10, 2018 www.jlr.org Downloaded from addition, the formation of presynaptic SNARE complexes, the interaction between synaptobrevin and synaptophysin, the fusion of synaptic vesicles with presynaptic membranes, and the sorting of synaptic vesicles during endocytosis all depend on cholesterol (120)(121)(122)(123)(124).…”
Section: Models Used For Studying Npc Diseasementioning
confidence: 99%
“…Recently, a mouse model with a point mutation in NPC1 (D1005G) has been described [94], and mouse models with other mutations are being developed. These mouse models will provide the capability of testing HDACi therapy in mouse models.…”
Section: Prospectivementioning
confidence: 99%